Does Digital Financial Inclusion Promote Innovation among Small and Medium-sized Enterprises? - Zhang, Xuheng (International Journal of Social Sciences and Public Administration, 2024)
In recent years, due to the rapid development of information technology and the Internet, digital inclusive finance has emerged based on Internet technology. Compared with traditional finance, digital inclusive finance has higher availability, wider coverage, and stronger sustainability, which is conducive to small and medium-sized enterprises to break financing constraints, broaden financing channels, and develop enterprise innovation. Therefore, this study selects relevant data on Chinese small and medium-sized enterprises from 2012 to 2020 to empirically test the impact of digital inclusive finance on the innovation of small and medium-sized enterprises. The empirical results show that: (1) The development of digital inclusive finance can significantly promote enterprise innovation; (2) Financing constraints play a partial mediating role in the process of digital inclusive finance promoting enterprise innovation.